Solvent-Free Ring Cleavage Hydrazinolysis of Certain Biginelli Pyrimidines - Mohamed A. Said; Wagdy M. Eldehna; Hazem A. Ghabbour; Maha M. Kabil; Nasser S. Al-shakliah; Hatem A. Abdel-Aziz (Journal of Chemistry)
Certain Biginelli pyrimidines with ester substitution in C5 were subjected to unexpected ring opening upon solvent-free reaction with hydrazine hydrate to give three products: pyrazole, arylidenehydrazines, and urea/thiourea, respectively. The nonisolable carbohydrazide intermediates are formed firstly followed by the intermolecular nucleophilic attack of terminal amino group of hydrazide function on sp2 C6 rather than the sp3 C4 to give the ring adduct which was produced as a final product.